Critics of economic basis of nationalism - V. A. Kapitanov; A. A. Ivanova (Статистика и экономика)
The purpose of the study is to verify the validity of the prevailing opinion about the existence of oppressed and oppressive peoples or, equivalently, about the cumulative causality of international inequality, or about the existence of rank exchange between peoples as independent decision-makers of economic entities. The paper analyzes the statics and dynamics of inequality in the per capita GDP of the countries of the world as a whole, the dynamics of international inequality in the “metropolitan-neocolonies” pairs on the examples of the USA-Latin American countries and France-CFA countries (former colonies of France in Africa), and the dynamics of inter-regional inequality Per capita income in Russia. For the study, the World Bank and Rosstat data were used. The degree of inequality in the world’s countries per capita GDP was compared with the degree of inequality of citizens of individual countries in terms of per capita income, found from indirect sources – distributions of prices for used cars in Russia and Germany. The need to use indirect data on the distribution of citizens by income is due to the incompleteness of official statistics. It is established that the inequality between the countries of the world is insignificant in comparison with the inequality of citizens in a single country. It is shown that, despite numerous examples of inequivalent transactions imposed by poor corporations of rich countries (regions), international inequality has declined since at least 1970, the inequality between France and the CFA countries has been declining since 1994, and between the United States and Latin America since 1960, Interregional inequality in Russia – since 1997. In conditions of rank exchange (cumulative causality of inequality), a long-term reduction in inequality is impossible: it can only grow, shrinking only during periods of crisis. As inequality declines, it was concluded that peoples (countries, regions) do not practice rank-sharing in relations with each other or, equivalently, the cause of international inequality is not cumulative. Statistical data do not confirm the existence of oppressed peoples and oppressor peoples and generally do not confirm the existence of “peoples” as monolithic economic entities acting in their own interests, since the people are not monolithic, but are divided by rank exchange into antagonistic classes. Unequal international transactions are often practiced, however, not between rich and poor peoples, but between representatives of exploiting and exploited classes, even if belonging to different peoples. The overwhelming majority of the so-called “oppressor people” refers to the exploited classes and is not the beneficiary of such transactions, otherwise international inequality would grow. Non-equivalent international transactions are often practiced, however, not between rich and poor peoples, but between representatives of exploiting and exploited classes, even if belonging to different peoples. The overwhelming majority of the so-called “oppressor people” refers to the exploited classes and is not the beneficiary of such transactions, otherwise international inequality would grow.